Response of Basil Growth and Morphology to Light Intensity and Spectrum in a Vertical Farm - Larsen, Dorthe H.; Woltering, Ernst J.; Nicole, Celine C. S.; Marcelis, Leo F. M. (Frontiers in Plant Science, 2020)
Vertical farming is becoming increasingly popular for production of leafy vegetables and herbs, with basil (Ocimum basilicum L.) as one of the most popular herbs. In basil most research has focused on increasing secondary metabolites with light spectra. However, knowledge about the effect of light intensity (photosynthetic photon flux density, PPFD) and spectra on growth and morphology is key for optimizing quality at harvest. The impact of PPFD and spectrum on plant growth and development is species dependent and currently few studies in basil are available. Understanding the response to end-of-production (EOP) light of growth and morphology is important for successful vertical farming. We performed a comprehensive series of experiments, where the effects of EOP PPFD, fraction of blue and their interaction on the growth and morphology were analyzed in two green and one purple basil cultivar. In addition, the impact of different EOP intensities and duration of far-red were investigated. We found that increasing the PPFD increased fresh mass, dry matter content and plant height in all three cultivars. The responses were linear or quadratic depending on the cultivar. A high fraction of blue (>90%) increased plant height and decreased the dry mass partitioning to the leaves. The only interaction found between the fraction of blue and overall PPFD was on plant height in the green cultivar whereas other growth parameters and morphology responded stronger to PPFD than to the fraction of blue light. Plant dry matter production was increased with the addition of far-red. Far-red EOP intensity treatments enhanced the fraction of dry mass partitioned to the leaves, whereas a prolonged far-red treatment enhanced partitioning to the stem. Both plant fresh mass and dry matter content were improved by applying high PPFD shortly before harvest. Light spectra were found to be of less importance than PPFD with respect to plant dry matter content. Light Use Efficiency (LUE) based on fresh mass decreased with increasing PPFD whereas LUE based on dry mass increased with increasing PPFD, when given as EOP treatments. The overall physiological mechanisms of the light intensity and spectral effects are discussed.